(untitled) (Research, Society and Development, 2021)
Objective: To analyze the variables related to the sociodemographic, clinical and reproductive aspects of post-discharge women for leprosy. Method: This is a cross-sectional analytical study with a quantitative approach, in which an instrument was constructed that contained data referring to the sociodemographic aspects and reproductive history of post-discharge women for leprosy during nursing consultations in Basic Health Units (UBS) from the county of Rio Largo, Alagoas, from April to July 2019. Results: The demographic and reproductive characteristics of the studied population were: predominantly brown women with low education (incomplete elementary) and illiterate, aged over 55 years, who perform household duties and with an income of 1 and a half minimum wages, in relation to clinical aspects 38.1% were diagnosed with undetermined clinical form and 66.7% paucibacillary. Conclusion: It was observed a need for special monitoring for women after leprosy discharge, since the vast majority of these women are of reproductive age. It is essential to promote care in order to prepare them for safe contraceptive practice and the prevention of high-risk pregnancies.